G203(P) Status dystonicus presenting in an acute setting in association with viral illnesses. (27th April 2015) - Jaleel, SA; Balfe, J; Curtis, E; McDonald, D
Abstract : Aims: We report 2 cases of status dystonicus seen in our hospital in 2014. Status dystonicus is a rare condition with a potentially life-threatening outcome. The patients' background, clinical features, management, likely triggers, differential diagnosis and outcome is discussed. Methods: Review of charts. Review of existing literature. Description: Case1 :A 9-year-old female with dystonic quadriparesis GMFCS class IV, intellectual disability and gastrostomy feeds was admitted with a febrile illness (pneumonia) and treated with intravenous antibiotics, oxygen and fluid support. Her dystonic movements had not required treatment before this. During the admission, she developed severe abnormal movements and unusual posturing with sustained hyperpyrexia, sweating and rising creatinine kinase (CK) > 23, 000. Blood and urine cultures were negative. She was intubated and ventilated, transferred to PICU, and received chloral hydrate, clonidine, and oseltamivir. She was subsequently confirmed as having Influenza A, H3N2 strain. During recovery, sedation was gradually weaned; however, dystonic movements recurred, requiring institution of a slower weaning regimen. She went home on trihexyphenidyl and remains well. Case2 : A 5-year-old male with microcephaly, spastic quadriparesis GMFCS class V (intra-thecal baclofen pump), visual impairment, profound intellectual disability, recurrent urinary tract infections (UTI), nephcalcinosis, gastrostomy feeds was admitted with Pseudomonas UTI and treated with ciprofloxacin. His recovery was complicated by norovirus gastro-enteritis with dehydration, pre-renal failure and increasingly severe dystonic posturing (tongue protrusion, sustained muscle contractions, ophisthotonus) with fever, sweating and rising CK (> 23000). He was treated with: transfer to HDU, close management of fluid and electrolyte balance, sedation with chloral hydrate, clonidine and midazolam. Resolution of the movement disorder and fever and normalisation of CK followed. He re-presented a month later with similar symptomatology; however, early treatment with hydration, clonidine and chloral hydrate appeared to halt progression to status dystonicus. He went home on low-dose clonidine and remains well. Conclusion: Status dystonicus is a rare condition with a high morbidity and mortality. A rising CK, severe dystonic movements and metabolic derangements suggest the diagnosis. Maintaining a high index of suspicion can identify such cases early and halt further progression. CK is simple test to monitor response to treatment.